S1701, A Randomized Phase 2 Trial of Carboplatin-Paclitaxel With and Without Ramucirumab in Patients With Locally Advanced, Recurrent, or Metastatic Thymic Carcinoma - Anne S. Tsao, MD, MBA; Ming-Hui Hsieh, MS; Marianna Koczywas, MD; Janet Tu, MD; Jonathan Riess, MD, MS; Tawee Tanvetyanon, MD; Barbara T. Ma, MD; Ying-Qi Zhao, PhD; Mary W. Redman, PhD; Martin J. Edelman, MD; David R. Gandara, MD; Jhanelle E. Gray, MD; et al. (JTO Clinical and Research Reports)
Introduction: Thymic carcinoma is a rare and aggressive malignancy with few treatment options. Preclinical studies suggested that targeting the angiogenic pathway may be beneficial in this disease. Methods: This randomized phase 2 trial enrolled patients with unresectable, locally advanced, recurrent, or metastatic thymic carcinoma. Patients were randomized to receive carboplatin-paclitaxel with or without ramucirumab. The primary end point was progression-free survival (PFS) and secondary end points included response by Response Evaluation Criteria in Solid Tumors, disease control, toxicity, and overall survival. The primary analysis was done using a one-sided 10%-level log-rank test. Target sample size was 66 patients. Results: Between 2018 and 2022, 21 patients enrolled to ramucirumab plus carboplatin-paclitaxel (RCP, n = 8) and to the control arm (carboplatin-paclitaxel [CP], n = 13) with one patient on CP not meeting eligibility criteria. Owing to slow accrual, the study was terminated early by the Data and Safety Monitoring Board. Of the 20 eligible patients, eight on RCP and nine on CP received protocol treatment. PFS was not statistically different (hazard ratio = 0.51, 80% confidence interval [CI]: 0.24–1.09, p = 0.13). There were no grade 4 or higher treatment-related adverse events with RCP, although 50% experienced grade 3 adverse events, in which one patient had a grade 3 thromboembolic event. Among nine assessable patients for toxicity on CP, one patient (11%) encountered grade 4 neutropenia and one patient (11%) reported grade 3 thromboembolic events. Response rates favored the RCP arm, with an 88% (seven of eight, 80% CI: 59%–99%) response rate compared with 40% (four of 10, 80% CI: 19%–65%) on CP arm (p = 0.04). Disease control rate was higher in the RCP arm (100% versus 70%, p = 0.09). At the time of analysis, as only one death has been reported, overall survival remains immature. Conclusions: Accrual to this population is challenging, and the study was closed early because of feasibility. Although PFS was not statistically better with RCP, the hazard ratio was 0.51 and the lack of significance was likely due to small sample sizes. Notably, addition of ramucirumab to CP led to higher response rates than CP alone. Future research should consider exploring larger multicenter trials and other combinations to improve outcomes. Challenges in enrollment emphasize the need for innovative strategies and larger collaborations in rare malignancies such as thymic carcinoma.